Análise fonológica em crianças em fase inicial de aquisição da linguagem durante a pandemia de covid-19 - Rodrigues, Camila Matos Pirote (2024)
The objective of this research is to investigate the possible effects of social isolation resulting from the COVID-19 pandemic on the phonological development of children aged 3 to 4 years. This is a descriptive, qualitative-quantitative, cross-sectional study that was carried out at an Early Childhood Education Center (CEI), located in Fortaleza, Ceará, from March to December 2023. The study was submitted to the Research Ethics Committee of the Federal University of Ceará, and was approved under opinion number 7.0000.5054. Based on the studies of Yavas (2001) and Lamprecht (2004), on the phonological acquisition of Brazilian Portuguese, Michael Tomasello (2003), and discussed from the Theory of Use-Based Language Acquisition that relates the acquisition and development of verbal repertoires to a biological and social process. The research was divided into 3 stages, for data collection, a questionnaire was initially applied addressing the prenatal, peri and postnatal, physical, social, cultural and emotional aspects seeking to understand how language acquisition occurred and the influence of the COVID-19 pandemic on its development. In a second moment, the structures of the stomatognathic system were evaluated, with orofacial myofunctional analysis in an adapted way through the protocol: Medeiros, Marchesan, Berrentin-Felix, Genaro, Rehder -Infants and preschoolers – MMBGR and, finally, the test: Andrade, Befilopes, Fernandes, Wertzner: Child language test in the areas of phonology, vocabulary, fluency and pragmatics – ABFW. The data were analyzed based on the inferential statistics of the data collected by the R program. The phonological processes found in this study demonstrated that the children used simplifying repair strategies below the expected for their chronological age, to deal with the difficulties in productions. These processes are common in development, but persistence beyond the expected age requires investigation and awareness of the effects of the pandemic on children's language development.